Perbanyakan dan Konservasi In Vitro Plasma Nutfah Talas (Colocasia esculenta (L.) Schoot) - Nurwita Dewi; Bambang S. Purwoko; Ida Hanarida; Agus Purwito; Iswari S. Dewi (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
Taro is a potential source of carbohydratefor anticipation of climate change. In vitro technology havenot been widely implemented for tuber crops conservation.Conservation of the crops is mostly conducted in field. Suchconservation is very susceptible to biotic and abiotic stress.The research consisted of two activities i.e: micropropagationand conservation. The objectives were to obtain taro invitro propagation and conservation method. The trial wasarranged in a factorial design with six replications. Five taroaccessions were used as the first factor for each study. Thesecond factor in propagation study was propagation mediumi.e: MS; MS + 2.9 μM IAA + 4.4 μM BA and MS + 2.9 μM IAA+ 22,2 μM BA. Shoot tip from taro sucker was used asexplant. The second factor in conservation study was MSmedium containing mannitol (0, 30, 40, and 50 g/l). Twoleavesin vitro shoots from micropropagation study was usedas explants. The addition of BA in MS medium + 2.9 μM IAAincreased the number of shoot of taro germplasm. The bestmedium for micropropagation of taro germplasm No. 21 andTalas Jahe is MS + 2,9 μM IAA + 4,4 μM BA, whereas thebest medium for No. 503, Talas Jahe and Lumbu Banten isMS + 2,9 μM IAA + 22,2 μM BA. Based on data of plantheight, percentage of leaf life and shelf life, MS medium +manitol 40 g/l was the best medium for taro germplasmconservation with prolong sub-culture interval.